2002
DOI: 10.1038/sj....bjc.6600214...
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear β-catenin expression is closely related to ulcerative growth of colorectal carcinoma

Abstract: Although most colorectal cancer develops based on the adenoma–adenocarcinoma sequence, morphologically, colorectal cancer is not a homogeneous disease entity. Generally, there are two distinct morphological types: polypoid and ulcerative colorectal tumours. Previous studies have demonstrated that K-ras codon 12 mutations are preferentially associated with polypoid growth of colorectal cancer; however, little is known about the molecular mechanism that determines ulcerative growth of colorectal cancer. β-cateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
4
13
1
Order By: Relevance
“…Similarly Wang et al, showed that nuclear β-catenin expression is a good prognostic marker in CRC development [11]. In accordance with our results, some other studies demonstrate the similar findings [36][37][38]. Upregulation of β-catenin has been found associated with exaggerated activity of Wnt signaling pathway [39].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly Wang et al, showed that nuclear β-catenin expression is a good prognostic marker in CRC development [11]. In accordance with our results, some other studies demonstrate the similar findings [36][37][38]. Upregulation of β-catenin has been found associated with exaggerated activity of Wnt signaling pathway [39].…”
Section: Discussionsupporting
confidence: 91%
“…Several observations support the importance of the activation of the Wnt/b-catenin signaling pathway in adrenal cortex tumorigenesis (11)(12)(13), as previously shown in a variety of human cancers (14)(15)(16)(17). In animal models, a constitutive activation of the Wnt/b-catenin pathway in the adrenal cortex of transgenic mice leads to the development of adrenocortical tumors with malignant characteristics (18).…”
Section: Introductionsupporting
confidence: 77%
“…The Wnt/b-catenin signaling pathway has been identified as one of the key signaling pathways in cancers (14)(15)(16)(17), having an essential pathogenic role in regulating cell growth, motility, and differentiation (29). Increasing clinical and scientific evidence supports the importance of the activation of this pathway in adrenal cortex tumorigenesis (11)(12)(13), as previously shown in a variety of human cancers (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although the mutations of the APC and β-catenin are rare in UC-related CRC, as compared with sporadic CRC, nuclear β-catenin expression is related to UCrelated CRC development. (39) Since the data on β-catenin mutation in UC-related CRC are limited, more studies are required to determine the role of the β-catenin mutation in UCrelated CRC. Also, expression of c-myc, cyclinD1 and c-jun, which are targets of the β-catenin/APC pathway, (17,40,41) may also influence colon carcinogenesis in the present model.…”
Section: Proteinmentioning
confidence: 99%